Treatment with parathyroid peptides and estrogen replacement for severe postmenopausal vertebral osteoporosis: prediction of long-term responses in spine and femur. - Reeve, J; Mitchell, A; Tellez, M; Hulme, P; Green, JR; Wardley-Smith, B; Mitchell, R (2001)
Fifteen women with severe vertebral osteoporosis were treated with daily parathyroid peptide (hPTH) plus hormone-replacement co-therapy (HRT) for 1 year. Eight other patients were randomized to HRT alone. Co-therapy with hPTH and HRT resulted in an impressive mean treatment response at the spine (dual-energy X-ray absorptiometry DXA) 15% above baseline; P < 0.015 compared with the HRT group) at 2 years, while at the proximal femur and radius there were smaller increases. hPTH co-therapy led to a significantly positive metabolic calcium balance at 1 year (by 2.13 mmol Ca/day, equivalent to a 5% annual increment in total body calcium; P = 0.015). The magnitude of the lumbar spine DXA response at 2 years depended statistically on the increase in bone formation rate, measured with 85Sr (r2 adjusted 0.48; P < 0.005) and patients with a large spine DXA response had larger calcium balance improvements (P < 0.03). Plasma osteocalcin changes tracked closely with increases in bone formation rate (r2 = 0.87). In seven patients treated throughout with HRT alone, and in eight hPTH-treated patients (three of whom switched to bisphosphonate therapy at year 4). DXA spine changes seen in years 3-5 were minimal, with no evidence of a statistically significant difference between groups. It is concluded that hPTH or comparable PTH receptor activators remain the most promising anabolic treatment for osteoporosis currently under clinical evaluation and a 6- or 12-month measurement of bone formation or a marker predicts the 2-5 year bone density outcome. Post-hPTH treatment, loss of bone appeared preventable with anti-resorptive therapy.